LONGER MASTICATION CYCLES TEND TO LOWER POST-PRANDIAL BLOOD SUGAR LEVELS - Ike Rahmawaty Ali; Siska Nia Irasanti (Fakultas Kedokteran Gigi Unjani, 2021)
Diabetes Mellitus (DM) is a metabolic syndrome occurred because of the lack of insulin hormone secretion or some factors disturbing insulin hormone or both of them. The mastication cycle is one of the factors related to the increasing in blood glucose. The research aims to analyse the relation between mastication cycle and DM risk factor on Faculty of Medicine students, Universitas Islam Bandung. The methodology was an experimental study. The subjects were 18 male Faculty of Medicine, Unisba, who fulfil the inclusive and exclusive criteria. First, scanning was conducted to know DM risk by questioners. Those students were divided into three groups of mastication cycle (15,30,45 cycle). Each group consisted of six students. The result showed that the tendency of average blood sugar was lower in the group with 45 cycles of mastication, compared to 30 and 15 cycles (86.5 vs 89.5 vs 92 mg/dL). However, according to a statistical calculation, there was no significant relationship between the mastication cycle and blood glucose (P =0.413; P>0.05). The average blood insulin level of 45 times the mastication cycle was the lowest compared to 30 and 15 mastication cycles (2.44 vs 2.97 vs 3.58 μg/ml). The result was that the mastication cycle was longer than the initial insulin release to work in the cell more effectively. In conclusion, DM needs to do more cycle in mastication food to maintain glucose in the blood. DOI : 10.54052/jhds.v1n1.p11-18